2016
DOI: 10.1158/0008-5472.can-15-3420
|View full text |Cite
|
Sign up to set email alerts
|

RPL23 Links Oncogenic RAS Signaling to p53-Mediated Tumor Suppression

Abstract: The ribosomal protein (RP)-MDM2 interaction is a p53 response pathway critical for preventing oncogenic c-MYC-induced tumorigenesis. To investigate whether the RP-MDM2-p53 pathway is a broad anti-oncogenic mechanism, we crossed mice bearing an MDM2C305F mutation, which disrupts RPL11 binding to MDM2, with mice expressing an oncogenic HrasG12V transgene. Interestingly, the MDM2C305F mutant mice, which are hypersensitive to c-MYC-induced tumorigenesis, are not hypersensitive to oncogenic HrasG12V-induced tumorig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Interestingly, most of the alternative spicing events occurred in ribosomal protein and TPT1 (TCTP) genes, whose normal transcripts are also highly expressed and enriched in the EVs (see above). While we do not see any splice variant forms of ribosomal or TCTP proteins in our datasets it is interesting to speculate that the corresponding transcripts we observe in EVs may be translated upon EV uptake in recipient cells; this, in turn, may contribute to onset of apoptosis and cancer, as described elsewhere353637.…”
Section: Resultsmentioning
confidence: 55%
“…Interestingly, most of the alternative spicing events occurred in ribosomal protein and TPT1 (TCTP) genes, whose normal transcripts are also highly expressed and enriched in the EVs (see above). While we do not see any splice variant forms of ribosomal or TCTP proteins in our datasets it is interesting to speculate that the corresponding transcripts we observe in EVs may be translated upon EV uptake in recipient cells; this, in turn, may contribute to onset of apoptosis and cancer, as described elsewhere353637.…”
Section: Resultsmentioning
confidence: 55%
“…Generally, activated p53 interacts with its tumor-inhibitory partners to initiate the growth-restricting pathways and repair DNA mismatches [187]. Specifically, as the downstream target of RP-MDM2 axis, p53 directly antagonizes RAS-involved tumorigenesis in rodent melanoma models [188]. Moreover, restoration of p53 could enhance the chemosensitivity of skin cancer cells by inducing the production of NEAT1 paraspeckles [189].…”
Section: Functions Of Ampk Signaling Components In Tumorigenesismentioning
confidence: 99%
“…RPL5, RPL11 and RPL23 bind to MDM2 simultaneously, forming a heterotetramer within cells . Although knockdown of RPL5 or RPL11, but not RPL23, markedly inhibits Act D-driven p53 induction (Bursac et al, 2012;Nicolas et al, 2016), evidence suggests that RPL23 functions as a tumor suppressor (Meng et al, 2016;Zhang et al, 2010Zhang et al, , 2013. The present data suggest that GRWD1 acts together with the E3 ubiquitin ligase EDD [also known as human (h)HYD or UBR5] and proteolytically regulates RPL23, and that this regulatory mechanism may play a role in p53 downregulation by GRWD1.…”
Section: Introductionmentioning
confidence: 52%
“…In addition, RPL23 inhibits MDM2 ubiquitin ligase activity. Therefore, RPL23 may act as a tumor suppressor Jin et al, 2004;Meng et al, 2016;Zhang et al, 2010Zhang et al, , 2013. By contrast, our previous study identified GRWD1 as a novel negative regulator of p53 and a potential oncogene .…”
Section: Grwd1 Modulates Mdm2 Protein Levels By Regulating Rpl23mentioning
confidence: 57%